Adverse selection in deposit insurance and government funding following the 2023 banking crisis - Huberdeau-Reid, David A.; Pennacchi, George G. (Journal of Financial Intermediation, 2025)
We examine whether U.S. banks whose uninsured deposits were subject to greater risk of loss prior to the March 2023 banking crisis used institutional mechanisms to expand their deposit insurance or accessed government funding after the crisis. We construct a bank-level measure of pre-crisis uninsured depositor risk incorporating financial statements, unrealized security losses, and estimates of unrealized loan losses that predicts a bank’s post-crisis loss of uninsured deposits. We find that riskier small and midsize banks tended to utilize reciprocal, sweep, and brokered deposits, but not listing service deposits, to attract more insured deposits. Riskier small and midsize banks temporarily accessed FHLB advances while only risky midsize banks borrowed from the Discount Window. Risk did not predict banks’ use of Fed BTFP funding. Riskier banks, particularly small and midsize ones, paid relatively higher interest rates on many types of deposits.